2017
DOI: 10.1038/s41598-017-05969-8
|View full text |Cite
|
Sign up to set email alerts
|

A new marine-derived sulfoglycolipid triggers dendritic cell activation and immune adjuvant response

Abstract: Dendritic Cells (DCs) recognize infectious non-self molecules and engage the adaptive immune system thereby initiating long lasting, antigen-specific responses. As such, the ability to activate DCs is considered a key tool to enhance the efficacy and quality of vaccination. Here we report a novel immunomodulatory sulfolipid named β-SQDG18 that prototypes a class of natural-derived glycolipids able to prime human DCs by a TLR2/TLR4-independent mechanism and trigger an efficient immune response in vivo. β-SQDG18… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
78
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 51 publications
(87 citation statements)
references
References 60 publications
4
78
2
Order By: Relevance
“…Most of these compounds act as vaccine adjuvants improving the immune response by activating APCs [7,49,58]. In Table 1, we have summarized the algae which have shown immunostimulatory activity.…”
Section: Microalgae With Immunomodulatory Activitymentioning
confidence: 99%
See 3 more Smart Citations
“…Most of these compounds act as vaccine adjuvants improving the immune response by activating APCs [7,49,58]. In Table 1, we have summarized the algae which have shown immunostimulatory activity.…”
Section: Microalgae With Immunomodulatory Activitymentioning
confidence: 99%
“…For instance, it was demonstrated that they are potent glutaminyl cyclase inhibitors, with possible applications against Alzheimer's disease [76]. In addition, sulfolipids have been shown to be able to activate the immune system, with application as vaccine adjuvants [7]. In particular, Manzo et al [7] used microalgae-derived sulfolipids as lead compounds to generate a synthetic sulfoglycolipid (called β-SQDG18) as vaccine adjuvant to trigger a more effective dendritic cell (DC) activation and improve immune response against cancer cell (i.e., B16 mouse melanoma cells).…”
Section: Sulfolipidsmentioning
confidence: 99%
See 2 more Smart Citations
“…In the recent years, microalgal lipid extracts have gained attention as they can act as immunogenic compounds. β‐Sulfoquinovosyl diacylglycerols (β‐SQDG18), a synthetic analog of α‐SQDG from microalgae Thalassiosira weissflogii , effectively stimulates the immune response by inducing the maturation of dendritic cells resulting in cytokine production (Manzo et al., ). Apart from antioxidant and anti‐inflammatory activities, microalgae also possess antimicrobial properties.…”
Section: Pharmaceuticalsmentioning
confidence: 99%